Deterministic generation of entanglement in a quantum network by coherent absorption of a single photon - Vetlugin, Anton N. (2023)
Advanced quantum information protocols rely on the operation of multinodal quantum networks where entanglement is distributed across the nodes. Existing protocols of entanglement generation are probabilistic, with the efficiency dropping exponentially with the size of the system. We formulate an approach for the deterministic generation of entangled states of a multinodal quantum network of arbitrary size by coupling a single photon standing wave with the nodes of the network. We show experimentally how this can be implemented in a simple binodal system. Since this approach relies on collective excitation of the network - not on local interaction with individual nodes - it allows generation of entanglement with unitary efficiency, independent of the size and the nature of the network.